The Presence of Previous Cerebral Microbleeds Has a Negative Effect on Hypertensive Intracerebral Hemorrhage Recovery - Yang, Kang; Feng, Yulan; Mu, JinJin; Fu, Ningzhen; Chen, Shufen; Fu, Yi (Frontiers in Aging Neuroscience, 2017)
Background and purpose: Cerebral microbleeds are an intracerebral microangiopathy with bleeding tendency found in intracerebral haemorrhage patients. However, studies about cerebral microbleed effects on the prognosis of hypertensive intracerebral haemorrhage patients are rare. We performed a prospective study to discuss not only the risk factors of cerebral microbleed incidence in hypertensive intracerebral haemorrhage patients but also the relevance of cerebral microbleeds with silent brain infarction, haemorrhage and prognosis. Methods: This study enrolled 100 patients diagnosed with hypertensive intracerebral haemorrhage within 3 days after onset. Magnetic resonance imaging including susceptibility-weighted imaging and diffusion-weighted imaging were utilized to examine patients on the fifth day after onset. Regular follow-ups were performed to examine the following clinical cerebrovascular events and vascular deaths in 1 year. Results: Cerebral microbleeds were observed in 55 (55%) patients. Multiple logistic regression analysis showed that over-aging, elevation of serum creatinine and leukoaraiosis were independently associated with cerebral microbleeds. In addition, higher silent brain infarction prevalence was observed in patients with cerebral microbleeds. In contrast, none of the cerebral microbleed patients exhibited cerebral microbleeds ≥5, which is an independent risk factor of poor 3-month neurological function recovery. During the 1-year follow-up, 14 subjects presented clinical cerebrovascular events or vascular death. The Cox proportional hazards model implicated that atrial fibrillation, cerebral microbleeds ≥5 and silent brain infarction were independent predictive factors for these events. Conclusions: Over-aging combined with an elevation of serum creatinine and leukoaraiosis were independent risk factors of cerebral microbleeds. Patients with cerebral microbleeds were more likely to exhibit silent brain infarction. Poor recovery of 3-month neurological function was observed in hypertensive intracerebral haemorrhage patients with cerebral microbleeds ≥5. Cerebral microbleeds ≥5 or silent brain infarction might also indicate an elevated risk of future cerebrovascular events and vascular death.